Electroreductive synthesis of polyfunctionalized pyridin-2-ones from acetoacetanilides and carbon disulfide with oxygen evolution. Issue 5 (19th January 2022) - Xu, Lichun; Ma, Zhongxiao; Hu, Xi; Zhang, Xin; Gao, Shulin; Liang, Deqiang; Wang, Baoling; Li, Weili; Li, Yanni
Abstract : A reductant-free electroreductive synthesis of polyfunctionalized pyridin-2-ones under the combined action of electro/copper/base with O2 evolution. Abstract : A chemical reductant or a sacrificial electron donor is required in any reduction reactions, generally resulting in undesired chemical waste. Herein, we report a reductant-free reductive [3 + 2 + 1] annulation of β-keto amides with CS2 enabled by the synergy of electro/copper/base using water as an innocuous anodic sacrifice with O2 as a sustainable by-product. This electrochemical protocol is mild and provides access to polyfunctionalized pyridin-2-ones from simple starting materials in a single step.